2013
DOI: 10.1111/cdev.12174
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Adolescents' Disclosure and Information Management With Parents

Abstract: Adolescents' obligation to disclose and their actual disclosure about their activities to parents, justifications for nondisclosure, and strategies for information management were examined in different domains in 460 middle adolescents (M(age) = 16.6 years) from working and middle-class families in Japan. Adolescents felt most obligated to disclose prudential issues, but disclosed most about personal issues. Adolescents primarily justified nondisclosure with claims to personal choice and for prudential issues,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 20 publications
1
13
0
4
Order By: Relevance
“…Lorsque les sujets étaient d'ordre prudentiel ou régulé socialement (c.-à-d., moraux et conventionnels), les adolescents estimaient que l'autorité parentale était légitime et, en retour, ils se sentaient en quelque sorte obligés de dévoiler des informations (p. ex., Nucci, Smetana, Araki, Nakaue, & Comer, 2014 ;Smetana & Metzger, 2008 ;Smetana et al, 2006). Par contre, lorsque les sujets étaient d'ordre personnel, les adolescents ne se sentaient pas obligés de se confier.…”
Section: Domaines De Discussion : Variation Selon La Légitimité Accorunclassified
“…Lorsque les sujets étaient d'ordre prudentiel ou régulé socialement (c.-à-d., moraux et conventionnels), les adolescents estimaient que l'autorité parentale était légitime et, en retour, ils se sentaient en quelque sorte obligés de dévoiler des informations (p. ex., Nucci, Smetana, Araki, Nakaue, & Comer, 2014 ;Smetana & Metzger, 2008 ;Smetana et al, 2006). Par contre, lorsque les sujets étaient d'ordre personnel, les adolescents ne se sentaient pas obligés de se confier.…”
Section: Domaines De Discussion : Variation Selon La Légitimité Accorunclassified
“…While Tilton-Weaver (2014) found that relationship dynamics and adolescent delinquent behaviors play a role in adolescents’ information management, she suggested that future research should sample more divergent cultures where strong expectations to conform to the rules and expectations of parents and other adults might affect this relationship. In one study with Japanese adolescents, levels of adolescent disclosure to parents, and perceptions of the obligation to disclose to parents were less than typically found in U.S. adolescents (Nucci et al 2014). These authors interpreted these results to reflect a cultural tendency in Japan to view adolescents’ actions as matters of personal responsibility.…”
Section: Introductionmentioning
confidence: 90%
“…Some studies of adolescents' disclosure and parental authority acknowledge the complexity of peer relations by branding them as ''multifaceted'' rather than clear exemplars of the personal, prudential, or conventional domains (Nucci et al 2014). Moreover, parents and adolescents often disagree about the domain into which a particular facet of peer relationships falls (Smetana et al 2006).…”
Section: Salience Of Peer Relationsmentioning
confidence: 99%
“…A hallmark of adolescence in the dominant US culture is the inclination to spend more time with peers and less with family. As adolescents' interactions and relationships with peers expand, they have more information to share with parents, but also possibly more to hide if they fear that parents will disapprove and seek to curtail their peer interactions (Nucci et al 2014;Stattin and Kerr 2000). Thus, it is unclear whether higher levels of peer involvement will increase or diminish disclosure of information to parents.…”
Section: Possible Predictors Of Rates Of Disclosure About Peersmentioning
confidence: 99%